Humanitarian cooperation between Great Britain and the Soviet Union in 1979-1985 - Viktoriia Sadykova (Cхід)
The aggressive foreign policy of the Soviet Union and insufficient dynamic development of Soviet culture of the late 70's of XX century led to a slowdown in the British-Soviet cultural relations, including the prohibition of exchange visits between Ministers of Culture of both countries and bilateral tours of theatre, ballet and opera groups. In order to otrengthen cultural relations between the UK and the Soviet Union, the leadership of both countries established centers of cultural developments like the British Association "Great Britain - USSR" and the Soviet Society "USSR - United Kingdom (UK)". Top priority areas of bilateral relations between the leadership of the United Kingdom and the Soviet Union were literary industry which included publishing scientific literature, expansion of book exchange between Soviet and British libraries, exhibitions of works of literature, such as the exhibition of the works of British authors, published on the territory of the Soviet Union in 1984; theatrical sphere, which included exchange visits of the UK and the USSR theater personalities (F. Dunlop, T. Holt, O. Yefremov T. Lavrov, A. Bartoshevycha) to study the trends of Performing Arts and review of countries' repertoire; contacts in the field of historical sciences by creating among States bilateral commission of historians of the USSR and the UK; research work done by Soviet specialists in the territorial waters of the United Kingdom with the permission of the British government; cooperation in the field of cinema presented directors and actors exchange visits of both countries carrying out the Soviet television Week in 1984 in the National theater of Great Britain; and constructive cooperation in the field of music, which demonstrated the International Music Festival in May 1981 in Moscow and performances of the Moscow Philharmonic, "Music of Russian rites and festivals" and "Tradition of ancient Russian music" in the early 1980's in UK. British-soviet system of contacts in the sphere of culture was a tool for establishing successful diplomatic relations between Great Britain and the Soviet Union.